Policy Uncertainty in Japan - Arbatli Saxegaard, Elif (IMF Working Papers; Working Paper, 2017)
We develop new economic policy uncertainty (EPU) indices for Japan from January 1987 onwards building on the approach of Baker, Bloom and Davis (2016). Each index reflects the frequency of newspaper articles that contain certain terms pertaining to the economy, policy matters and uncertainty. Our overall EPU index co-varies positively with implied volatilities for Japanese equities, exchange rates and interest rates and with a survey-based measure of political uncertainty. The EPU index rises around contested national elections and major leadership transitions in Japan, during the Asian Financial Crisis and in reaction to the Lehman Brothers failure, U.S. debt downgrade in 2011, Brexit referendum, and Japan's recent decision to defer a consumption tax hike. Our uncertainty indices for fiscal, monetary, trade and exchange rate policy co-vary positively but also display distinct dynamics. VAR models imply that upward EPU innovations foreshadow deteriorations in Japan's macroeconomic performance, as reflected by impulse response functions for investment, employment and output. Our study adds to evidence that credible policy plans and strong policy frameworks can favorably influence macroeconomic performance by, in part, reducing policy uncertainty.